Unlimited Limites (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
Through this manuscript, we try to analyse the work entitled Unlimited Limits as well as expose our experience as its authors. Therefore, we approach this analysis from the action itself and not from the consequence of that action. If we analysed Unlimited Limits as if it was closed (its “what”), we would be ignoring part of its reality (its “how”), the experience. Thus, the text that continues aims to expose not only the motivations and tensions that may arise during the implementation of a work that dialogues with its direct environment, it also tries to offer an approach to the experience that the launch of the project that combines performance and drawing entails.
Keywords: Drawing; Performance; Thinking; Line; GPS